Differences in miRNA expression profiles between GIST and leiomyoma in human samples acquired by submucosal tunneling biopsy - Fujita, Koji; Kobara, Hideki; Mori, Hirohito; Fujihara, Shintaro; Chiyo, Taiga; Matsunaga, Tae; Nishiyama, Noriko; Ayaki, Maki; Yachida, Tatsuo; Morishita, Asahiro; Fujiwara, Masao; Okano, Keiichi; Suzuki, Yasuyuki; Iwama, Hisakazu; Masaki, Tsutomu (Endoscopy International Open, 2015)
Background and study aims: Small gastrointestinal stromal tumors (GISTs) rarely have malignant potential with poor prognosis. Using conventional imaging to differentiate between small GISTs and leiomyoma, which often have similar characteristics, is difficult but essential in daily practice. Although some studies have reported on the utility of serum c-kit as a biomarker for non-small GIST and specific miRNA, clinical aspects of such testing are controversial. The aim of this study was to identify differences between small GIST and leiomyoma through the investigation of miRNA expression patterns in human cases. Patients and methods: MiRNA expression was examined in nine GIST (less than low risk, mean 18 mm in size) samples and seven leiomyoma samples acquired by a novel sampling method, submucosal tunneling biopsy (STB), which produces tumor specimens of submucosal tumor (SMT) without contamination of sufficient size to be examined under direct vision. Total RNA was extracted from these tissues and analyzed for miRNA expression patterns by microarray. Subsequently, real-time quantitative polymerase chain reaction (qPCR) were used to confirm specific miRNA overexpression, comparing GISTs with leiomyomas. Results: Microarray analysis revealed upregulation of the miR-140 family up to 20 times higher in GISTs than in leiomyomas. Real-time qPCR revealed that the expression level of miR-140-5 p in GISTs was 27.86 times higher than in leiomyomas; miR-140-3 p was 12.24 times higher as well. Conclusions: The STB method provided suitable SMT samples for miRNA analysis. MiR-140 family members may serve as specific biomarkers to distinguish GIST from leiomyoma.